EFFECT OF MUTAGENS ON BIOMASS AND LIPID CONTENT OF ULOTHRIX sp. AND OSCILLATORIA sp. FOR IMPROVED BIODIESEL production - N. Munir; M. Samad; N. Sharif; R. Haq; S. Naz (Journal of Animal and Plant Sciences, 2023)
Chemical and physical mutagens like sodium azide, H2O2 and UV light have a significant role in the metabolism of living organisms. Effect of these mutagens was recorded during the present work on lipid content of Oscillatoria sp. and Ulothrix sp. The algal species were subjected to the mutagens by adding them in culture media. Lipids were extracted by Microwave- assisted extraction using methanol, ethanol and chloroform. During the present work generally a significant effect of algal species and mutagens was observed. All the tested mutagen significantly affected the lipid content. A significant effect of solvent on lipid content of algal species was observed when the algae were extracted with different solvents after treatment with H2O2 and UV light however this effect was non-significant when algae were subjected to sodium azide. . In general, the mutagen resulted in an increase in lipid content. In Oscillatoria sp. the lipid content was generally less as compared to Ulothrix sp. The highest lipid content of 0.5433±0.002 g100g-1 was recorded in Ulothrix sp. after 3 days stress of sodium azide stress followed by H2O2 treated (50mM) samples with a content of 0.5133±0.05g100g-1. In Oscillatoria sp. 15mM treatment for 3 days gave a lipid content of 0.3733±0.0001g100g-1 after 3 days. A reduction in fresh weights of both tested algal species was recorded after UV stress. The oil content also showed a significant reduction after UV exposure. GC-MS analysis of the transesterified lipids showed that different fatty acids show variation when algal samples were treated with mutagens. Hence this study is helpful in manipulation of algal oil for biodiesel production.
Keywords: Mutagen; Oscillatoria; Transesterification; Ulothrix